The Effect of Health Literacy Using Snakes and Ladders on HIV/AIDS Against Adolescent Risk Behavior - Eny, Eny; Dwiyanti, Danik; Kunaryanti, Kunaryanti (Miracle Journal of Public Health, 2024)
In 2022, Waimital Village recorded 4 HIV cases among adolescents, two of whom died. Preliminary research indicated that these cases were influenced by low health literacy among adolescents. This study aims to analyze the relationship between health literacy using Snakes and ladders media about HIV/AIDS and risky behavior among adolescents. This study used a quantitative design with a Quasi-Experimental approach. The study population was 123 adolescents, and the sample was calculated using the Lameshow formula to obtain 56 respondents. Data were analyzed using the Wilcoxon test because the data distribution was unexpected. The results showed a significant relationship between health literacy and adolescent behavior after the intervention (p-value=0.048). Two interventions using Snakes and Ladders media effectively improved health literacy and influenced adolescents' actions toward risky behaviors. It is expected that health centers, village officials, and schools can implement health literacy programs directly and consistently to reduce risky behaviors in adolescents.